SELECTED FORMS OF ECONOMIC BEHAVIOUR OF MEMBERSIN RURAL HOUSEHOLDS WITH A DISABLED PERSON - Agnieszka Siedlecka; Jarosław Żbikowski; Marek Kuźmicki (Annals of the Polish Association of Agricultural and Agribusiness Economists)
All subjects that exist in a given economic system show to a greater or lesser degree various formsof economic behaviour. The main aim of this study is to analyze selected forms of economic behaviourin rural households with disabled people. In particular, the author presents a thorough analysis of waysof generating income by people living in such households. Taking into consideration the spatial scope ofthe research, it seems legitimate to assume that work in agriculture the predominant source of income inthe analyzed households. Another hypothesis formulated in this study is the assumption that the sourcesof income in households with a disabled person are determined by the degree of disability and the periodof legal disability status granted in a medical certificate. In order to verify the hypothesis, the authorconducted survey studies of 5000 households with disabled people. The analysis allowed for a positiveverification of only the second hypothesis.